Scattering-type near-field optical microscopy characterization of topological insulator Bi2Te3 nanowires - Johnson, D; Vincent, T; Liu, X; Gholizadeh, B; Schoenherr, P; Hesjedal, T; Kazakova, O; Huáng, N; Boland, J (IEEE, 2023)
Topological Insulator (TI) devices have potential applications in spintronic and low-loss communication devices. However, they are difficult to characterize with standard far-field spectroscopy due to contributions from both the surface and the bulk. Utilizing the surface-sensitive scattering type Scanning Nearfield Optical Microscopy (s-SNOM) technique coupled with high surface-to-volume ratio structures such as nanowires, the local dielectric function and electro-optical properties of the metallic surface states of TI candidate Bi 2 Te 3 are investigated. We demonstrate spectral resonant features at 1250 cm −1, which are imaged with nanoscale resolution.